IKLAN LAYANAN MASYARAKAT TENTANG NOMOPHOBIA DENGAN TEKNIK MOTION GRAPHIC - Surya Agung Perdana; Zubaidah A Zubaidah A (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Nomophobia (No Mobile Phobia) is a form of phobia in the form of fear and anxiety that occurs if someone does not hold a phone or gadget for a short time, so that it can cause stress. This condition is not only afraid of losing the smartphone but also runs out of battery and does not get the network. Excessive use of smartphones will have a negative impact on physical and psychological health. To provide an awareness and knowledge effort for the public about the information on the danger of gadget or nomophobia dependence, it is necessary to make a media with the title "Public service announcement about nomophobia with Motion Graphic Technique".The method of designingsmotionsgraphicspublicsservice announcements about nomophobia uses the method of designing glass boxes. The results of the design of public service ads about nomophobia with motion graphic techniques in the form of video format H264 or MP4 with HDTV resolution of 720p 25fps and promoted on social media Youtube and Instagram. In addition to the main media, this design also uses supporting media in the form of posters, mugs, pins, x-banners, stickers, t-shirts, totebags and tumblers.Thewresultswofwthewdesign arewexpected towbe one of the efforts to disseminate information to the public about the negative impacts caused by Nomophobia. Furthermore, public service announcements are expected to broaden people's horizons to be more aware of the dangers posed by NomophobiaKeywords : Public Service Advertisements, Motion Graphic, Nomophobia